﻿Sexual dimorphism in postcloacal scales in the northern caiman lizard (Dracaena guianensis) - Riccardo Antonini; Rupert Kainradl; Michaela Gumpenberger; Anton Weissenbacher; Doris Preininger (Herpetozoa, 2023)
Morphological differences between males and females are common among reptiles. A particularly interesting sexually dimorphic feature whose function is largely unknown is the number and pattern of specific scales. Several lizard species possess an arrangement of centered scales near the cloacal region that differ between the sexes and can be used for sex determination. The presence of postcloacal buttons, sexually dimorphic postcloacal scales on both sides of the body, is an exclusive trait in the subfamily Tupinambinae and is only poorly documented. Here, we investigate postcloacal scales in northern caiman lizards (Dracaena guianensis) housed at the Vienna Zoo. For a period of two years, we documented scale patterns and performed morphometric measurements of individuals of different age classes. Caiman lizards were CT scanned to confirm the sexes. Males exhibit three raised postcloacal scales in a row behind the left and right leg, while females possess one or two large scales surrounded by several smaller scales. The study provides the first evidence that these scales can function as a reliable trait to distinguish the sexes regardless of age or reproductive status. The sexually dimorphic bilateral scale pattern is present immediately after hatching and does not change during development. Scales only increase in thickness and length during growth. We further demonstrate that sexual size dimorphism (SSD) exists in juveniles during ontogenetic development. Juvenile females had a larger SVL, body length, tail length and higher weight compared to juvenile males. This SSD could not be confirmed in adults, and sex determination based on SSD seems unreliable.